Penyesuaian program peralihan dengan kerjaya pasca persaraan Angkatan Tentera Malaysia - Mohamed, Mahmood Nazar; Ariffin, Mohd Taib; Husin, Azizan (Universiti Utara Malaysia, 2003)
The Malaysian ex-servicemen are among the members of our community who experienced certain limitations with their post retirement careers.Most of the retired from the service are at an early productive age group but not many had succeeded in their second career.This study was done to identify the issues on implementation and ascertain the success of the pre-retirement program with their post-retirement career.Data was gathered from three sample groups in the states of Kedah and Selangor.The first group consists of 68 respondents who were serving their pre-retirement program, sampled twice before the program and three months after the program.The second group consists of 287 respondents who had completed their pre-retirement program and who are currently in their post-retirement careers.The third group consists of 49 employers who employed ex-servicemen as their trainees. The study identified that those who are still in the program stated discrepancies between courses which they prefer to attend, with programs which they applied to attend, programs which they attended and the probable career they would pursue after the program.This mismatch is especially prominent among the ex-servicemen who do not fulfill the service requirement as outlined in PMAT.The same observation is also true for the ex-servicemen who are already in their post-retirement career.However, the study also identified that there are general satisfaction towards the program and courses offered.The employers also expressed satisfactions with the general capabilities of the ex-servicemen working for them but hold some reservation of their knowledge at work and work attitude.A total of 59.7% reported they are unemployed or currently not holding any stable job, and with that, 0.7% are defined as not poor, 6.3% poor and 93.0% as borderline poor.This study also outlined several models to improve the operations and monitoring of the pre-retirement program for Malaysian ex-servicemen.